2020
DOI: 10.2174/1381612826666200730221446
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy Offers a Possible Safe and Promising Alternative Approach for Treating Vitiligo: A Review

Abstract: Background: Normal skin pigmentation pattern is an extremely important component of the appearance of a person, as it can be a significant factor in the social context of any person. A condition known as vitiligo is caused by the death of melanocytes leading to pigmentation loss in the skin. This affects all races across the globe and sometimes leading to social avoidance as in some communities it is stigmatized. Although there are different pathobiological processes suspected because of the different underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…In addition, MSCs can inhibit abnormally activated Th1 cells, restore the Th1/Th2 balance inhibit excessive proliferation of T cells and suppress the activity of cytotoxic CD8 + T lymphocytes via the NKG2D pathway. 53 Thus, MSCs can improve the immune status by regulating the function of multiple subtypes of T cells. 54,55 Lymphopenia is also a prominent feature of COVID-19, suggesting that SARS-CoV-2 infection causes T-cell imbalance.…”
Section: Mscs Broadly Suppress T-cell Activation and Proliferation Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, MSCs can inhibit abnormally activated Th1 cells, restore the Th1/Th2 balance inhibit excessive proliferation of T cells and suppress the activity of cytotoxic CD8 + T lymphocytes via the NKG2D pathway. 53 Thus, MSCs can improve the immune status by regulating the function of multiple subtypes of T cells. 54,55 Lymphopenia is also a prominent feature of COVID-19, suggesting that SARS-CoV-2 infection causes T-cell imbalance.…”
Section: Mscs Broadly Suppress T-cell Activation and Proliferation Inmentioning
confidence: 99%
“…MSCs can decrease the secretion of IFN‐γ and TNF‐α of T cells, and upregulate the secretion of IL‐4, so that the cells are transformed from a pro‐inflammatory state to an anti‐inflammatory state. In addition, MSCs can inhibit abnormally activated Th1 cells, restore the Th1/Th2 balance inhibit excessive proliferation of T cells and suppress the activity of cytotoxic CD8 + T lymphocytes via the NKG2D pathway 53 . Thus, MSCs can improve the immune status by regulating the function of multiple subtypes of T cells 54,55 .…”
Section: Potential Mechanisms Of Stem Cell Therapy In Covid‐19mentioning
confidence: 99%
“…Diseases. Recent studies demonstrate the remarkable therapeutic effectiveness of MSCs towards several other autoimmune diseases such as type 1 diabetes [77], multiple sclerosis [78], Hashimoto's autoimmune thyroiditis [79], autoimmune hepatitis, primary biliary cirrhosis [80], and vitiligo [81], among others. For example, MSCs have been shown to prevent inflammation and neurodegeneration in animal models of multiple sclerosis (MS).…”
Section: Application In Other Autoimmunementioning
confidence: 99%
“…So that it has been suggested that future preclinical and clinical investigations might be needed to consider and investigate other progenitor cells, including, MSCs, ESCs, and iPS [ 403 , 406 ]. In this case, prior studies have mentioned that MSCs could promote the regimentation process as they regulate the underlying immune response leading to the disease [ 407 ]. ADSC were also investigated as supporting graft in animal models that received MelSC transplantation; the co-transplantation of ADSCs and MelSC had more beneficial effects in comparison with monoculture MelSC [ 408 ].…”
Section: Introductionmentioning
confidence: 99%